2016
DOI: 10.1097/ana.0000000000000231
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Measurement of Cerebral Blood Flow Under Anesthesia Using Arterial Spin Labeling MRI: A Pilot Study

Abstract: ASL-MRI is a feasible, noninvasive method of quantitative estimation of global and regional CBF in mechanically ventilated patients under anesthesia. In this pilot study CBF was consistently greater with sevoflurane than with propofol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 22 publications
(22 reference statements)
2
10
0
Order By: Relevance
“…We hypothesised that the end-tidal gas profile resulting in the most stable rCVR might be considered for anaesthetic management and form the basis of further investigation to formulate a strategy to decrease neurological complications postoperatively. Supporting this contention is that the available BOLD MRI literature on anesthetised humans, 19–22 indicate similar rCVR–ETCO 2 interactions (but less comprehensively analysed) to those described here, indicating that this study in awake subjects has clinical crossover to the anesthetised state. Importantly, an extensive review of the impact of anaesthesia on CO 2 -CVR indicates that, in humans, cerebral reactivity to CO 2 is maintained with volatile and propofol anaesthesia at standard clinical doses 23 …”
Section: Introductionsupporting
confidence: 58%
“…We hypothesised that the end-tidal gas profile resulting in the most stable rCVR might be considered for anaesthetic management and form the basis of further investigation to formulate a strategy to decrease neurological complications postoperatively. Supporting this contention is that the available BOLD MRI literature on anesthetised humans, 19–22 indicate similar rCVR–ETCO 2 interactions (but less comprehensively analysed) to those described here, indicating that this study in awake subjects has clinical crossover to the anesthetised state. Importantly, an extensive review of the impact of anaesthesia on CO 2 -CVR indicates that, in humans, cerebral reactivity to CO 2 is maintained with volatile and propofol anaesthesia at standard clinical doses 23 …”
Section: Introductionsupporting
confidence: 58%
“…A recent study already evaluated ASL and anatomical imaging in direct comparison: here, ASL provided more accurate results than structural imaging only in a small patient cohort [ 19 ]. Another study evaluated the effects of anesthesia using ASL [ 20 ]. The latter could also become more interesting regarding changes of perfusion of tumors under anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…For example, an ASL study in 4 patients with Moyamoya disease found that halogenated anesthesia (sevoflurane) was associated with consistently higher global gray matter CBF. 48 In our study, intravenous propofol sedation, with or without mask induction using a halogenated anesthetic, was performed for all children 3 months to 6 years of age. Between 6 and 9 years of age, there were variable rates of sedation.…”
Section: Discussionmentioning
confidence: 99%